Keterpaduan Lintas Sektoral Dalam Pengembangan Kebijakan Integrated Water Resources Management (IWRM) pada Wilayah Sungai Aceh Meureudu Provinsi Aceh - Lely Masthura; Budi S Wignyosukarto; Nina Fahriana; Muhammad Zacky Ardhyan (Jurnal Daur Lingkungan, 2023)
Water resources management is a hot topic in the world. Integrated Water Resources Management is a process that integrates water management, land, and other related resources in a coordinated way to maximize economic and social welfare equally without sacrificing the sustainability of vital ecosystems. The principle is formulated in the form of integration of natural systems and human systems, the last concerning the cross-sectoral integrity in policy development; the integration of stakeholders in the process of planning and decision-making and cross-regional integrity. Various water resources management institutions exist in Indonesia, but follow-up in water management is still weak. Some inefficiencies occur in water management in Indonesia. Implementation of existing water policies has not been in accordance with existing laws. The bureaucratic structure is ineffective, thus not contributing to the development of water governance in Indonesia.  This study tries to compile and analysis of some best practices and constraints of interdependent relationships of stakeholders on the process of planning and decision making of integrated water management. The study took place at the Aceh-Meureudu River Basin in Aceh Province, which is one of the national-strategic river basins. The method used in this study was descriptive analytic which illustrate the inter-institution coordination at the river basin in water conservation activities, water resource utilization, and controlling the destructive power of water. The results of these compilations of water resources management in the river basin indicate the differences in implementation caused by differences in regulations between sectors at several district and provincial institutions, even though there is the scheme of water resources management made by and with the approval of Water Resources Management Coordination Team. Some of the planned management schemes were not implemented because of the conflict of regulations. The results of this evaluation should be input for improving the development of water resources management policies in the Aceh-Meureudu River Basin.